Global global development plan building peace, law or development project for Giant Huila? (2016)
Gigante Huila, a thriving municipality has lost prominence in recent years, its inhabitants cross the recession of false prosperity that would bring the construction of the hydroelectric El Quimbo, despite being geographically located in the central-eastern department of Huila, the municipality not he has achieved its development and is currently experiencing an economic and social crisis. In this situation we find the current Development Plan of the municipality of Gigante Gigante called Friendly Building Peace for the constitutional period 2016-2019 where we focus on the components of the diagnosis showing the current reality and the strategies proposed to solve the detected in the diagnosis, but it is evident that the diagnosis was needed closer to the community as several issues were left out and therefore strategies despite being focused on solving most evident difficulties in diagnosis, does not provide solutions to various issues facing the community; not equally high-impact strategies that achieve the transformation of the Municipality into a true development can be seen.